Multimodal travel behaviour, attitudes, and cognitive dissonance. (November 2022) - An, Zihao; Heinen, Eva; Watling, David
Highlights: Multimodal travellers tend to have more balanced attitudes towards various modes. Multimodal travellers may be more likely to be cognitive dissonant with their mode use. We provide psychological explanations for long-term modal changes amongst multimodal travellers. Supporting policies are required when encouraging multimodality is expected as a tool for inducing sustainable modal shifts. Abstract: Multimodal travel behaviour, also termed multimodality, refers to as the phenomenon of an individual using more than one mode of transport in a given period. Studies indicate that encouraging multimodality may provide a solution to induce modal shifts towards sustainable transport. In this research, we investigate the distribution of mode-specific attitudes and attitude-mode use incompatibilities across clusters and levels of multimodality using the Netherlands Mobility Panel. We find that the most positive attitude does not necessarily correspond to the mode with the highest level of use. Attitudes towards car use are most positive, independent of the cluster membership and levels of multimodality. We also find that multimodal public transport users (compared with car-dominant users) and those with a higher level of multimodality are more likely to be attitudinally incompatible with frequently-used modes and the composition of their existing mode sets of travelling. This suggests that multimodal individuals may tend to experience cognitive dissonance with their mode use. Our findings also help uncover the psychological mechanism underlying a recent important finding that multimodal individuals are inclined to change their mode use patterns over time.